2010
DOI: 10.1111/j.1528-1167.2010.02646.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral pregabalin as an add‐on treatment for status epilepticus

Abstract: Summary Oral antiepileptic drugs (AEDs) represent possible add‐on options in refractory status epilepticus (SE). In this setting, pregabalin (PGB) has not been reported before. Over the last 42 months, we identified 11 SE episodes (10 patients) treated with PGB in our hospital. Its use was prompted by the favorable pharmacokinetic profile, devoid of drug‐drug interactions. The patients mostly had refractory, partial SE. Only two patients were managed in the intensive care unit (ICU). We found a definite electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 11 publications
3
21
0
Order By: Relevance
“…Oxcarbazepine, carbamazepine, rufinamide, felbamate, pregabalin [45,Class IV], and others may also be added by nasogastric tube.…”
Section: Other Oral Antiepileptic Medicationsmentioning
confidence: 99%
“…Oxcarbazepine, carbamazepine, rufinamide, felbamate, pregabalin [45,Class IV], and others may also be added by nasogastric tube.…”
Section: Other Oral Antiepileptic Medicationsmentioning
confidence: 99%
“…Pregabalin (PGB) is only available as an oral agent, but it is considered as a potential option in treating RSE since it has a good safety profile, can be started at a high dose, does not interact with other AEDs and has good oral bioavailability. A preliminary study by Novy and Rossetti [19] showed that 5/11 patients with RSE demonstrated a clinical response to the addition of PGB after the patients were treated with a benzodiazepine and another AED. PGB has a different mechanism of action than PHT or LEV.…”
Section: Background and Significancementioning
confidence: 99%
“…Several studies already analyzed the efficacy of newer AEDs in SE (11)(12)(13)(14)(15)(16)(17)(18)(19)(20); however, besides a previous preliminary analysis by our group (20), little is known regarding the evolution over time in AEDs prescription patterns in SE, and its impact on clinical outcome. The aims of this study were to explore the changes in prescription of newer and traditional AEDs in SE treatment over the last decade, and their association with prognosis.…”
Section: Introductionmentioning
confidence: 98%